Design and Implementation of a Solar Power System on Grid SDN 023905 BIN JAI using PVSYST Software - Raihan Putri; Asri Asri; Rosdiana Rosdiana; Fakhruddin Ahmad Nasution; Wahyu Pujianto Trinanda (Majlesi Journal of Electrical Engineering)
Electricity is an indispensable requirement for modern society, and with the advancement of technology, the adoption of renewable energy sources, such as Solar Power Plants (PLTS), has been on the rise. PLTS harness the virtually limitless and abundant power of solar energy. The successful construction and operation of a Solar Power Plant necessitates meticulous planning to ensure optimal functionality. In our research aimed at PLTS development, we have chosen an on-grid operating system for installation on the roof of SDN 023905 Binjai. This decision aligns with our goal to reduce the reliance on conventional electrical sources at SDN 023905 Binjai, which currently receives its entire electrical supply from PLN. The proposed PLTS will boast a capacity of 1.2kWp, comprising four 300Wp solar panels connected in series, alongside a 1.2 kW to 3 kW inverter. Our comprehensive analysis validates the feasibility of this plan, as it yields a Performance Ratio (PR) of 84%, surpassing the minimum PR benchmark of 70%. From a financial perspective, the project entails an initial investment cost of IDR 31,555,222, with a remarkably swift payback period occurring within the first year and month of the PLTS's 20-year operational lifespan.